Hemostatic effect of combined procedures for placenta previa: cervix-holding, intrauterine balloon, and uterine compression suture. (12th December 2022) - Takahashi, Hironori; Baba, Yosuke; Usui, Rie; Suzuki, Hirotada; Horie, Kenji; Yano, Hitoshi; Ohkuchi, Akihide; Matsubara, Shigeki
Abstract: Objectives: Various procedures have been introduced to achieve hemostasis for postpartum hemorrhage (PPH) in placenta previa (PP). This study attempted to clarify the effectiveness of the combined use of three hemostatic procedures: Matsubara-Takahashi cervix-holding (MT-holding), intrauterine balloon (IUB), and uterine compression suture (UCS). Study design: This was a historical cohort study on the hemostatic effect of combined procedures for patients with placenta previa (PP) undergoing cesarean section between April 2006 and December 2018. Until 2011 (2006–2011), we used MT-holding alone, whereas since 2012 we have also been using IUB and UCS: MT-holding alone was used in the former period whereas three procedures (MT-holding, IUB, UCS, and their combinations) have been used in the latter period. Perinatal outcomes were compared between 2006–2011 (before group) and 2012–2018 (after group). Results: Of 416 patients with PP, excluding 273 patients with cesarean hysterectomy or no hemostatic procedure, the remaining 143 patients were analyzed. In the after group, intraoperative blood loss, the percentage of patients with postoperative blood loss ≥ 500 ml, and incidence of autologous blood transfusion were significantly lower than in the before group. Multivariate analysis showed that postoperative blood loss ≥ 500 ml decreased in the after group (adjusted OR: 0.3, 95%CI: 0.1–0.8, compared with the before group). Conclusion: PPH decreased after introducing the combination of hemostatic procedures in patients with PP. Further studies are needed to determine the best combination and optimal indication for combining hemostatic procedures for PP.